Reconceptualizing urban identity: a study of Hanoi's form and pattern languages from 1873 to 1902 - Nguyen, Ngoc Hong (Journal of urban design, 2024)
Urban identity has been an elusive challenge in urban studies. This research investigates Hanoi's identity from 1873 to 1902 employing a methodology grounded in pattern and form languages, alongside the newly-developed Coherent Index. It finds that Hanoi's late nineteenth-century form emphasized multiple scales, clear connections between urban elements, and the prominence of focal points and distinctiveness. The city's form has been shaped by the interdependence of social and political needs among its diverse populations, connection to nature, and prestige, security, and symbolism. This research broadens the scope of urban identity across diverse contexts, enhancing comprehension of its intricate nature.